2004
DOI: 10.1007/s00404-002-0411-7
|View full text |Cite
|
Sign up to set email alerts
|

Significance of CA 125 serum level in discrimination between benign and malignant masses in the pelvis

Abstract: . Preoperative determination of CA 125 is a very useful method to discriminate between benign and malignant masses in the pelvis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Previous markers which have been used for OVC, including CA125 and HE4, only detected OVC at the late stages of cancer development and lacked efficiency during early tumor growth (13,14). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous markers which have been used for OVC, including CA125 and HE4, only detected OVC at the late stages of cancer development and lacked efficiency during early tumor growth (13,14). …”
Section: Discussionmentioning
confidence: 99%
“…For example CA125 was discovered 20 years ago and has been used widely as an OVC marker since (13). However, CA125 has low specificity and sensitivity during the early stages of OVC (6,9,14), thus an ideal marker has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The role of CA 125 in differentiating cancer cases from benign condition is also reported in pelvic lesions and non-Hodgkin lymphomas [14,15].…”
Section: Discussionmentioning
confidence: 95%
“…Large screening trials for ovarian cancer indicate that using a CA125 cutoff value of 30 U/ml has good sensitivity, but inadequate specificity for detecting preclinical disease [15] . Because of concern about the specificity of the test, other reports suggested that the upper limit of the normal range for ovarian cancer screening should be 65 U/ml [13] . Mancuso et al [16] pointed out that, in the prediction of a malignant adnexal mass, the best results were obtained from the association between CA125 and menopause, probably because in this period there is a lower incidence of benign diseases related to this marker so that an increase in the CA125 level is more likely associated with a malignant mass.…”
Section: Discussionmentioning
confidence: 99%
“…Although a single CA125 measurement provides no advantage in the early detection of ovarian cancer in asymptomatic postmenopausal women [12] , a growing body of evidence has accumulated that preoperative determination of CA125 is a very useful method to discriminate between benign and malignant masses in the pelvis [13] . In one of the reported evaluations of CA125 screening, the sensitivity and specificity of CA125 alone for the diagnosis of ovarian cancer, at a cutoff level of 35 U/ml, were 83 and 82%, respectively [14] .…”
Section: Discussionmentioning
confidence: 99%